Pinniped- and Cetacean-Derived ETosis Contributes to Combating Emerging Apicomplexan Parasites (Toxoplasma gondii, Neospora caninum) Circulating in Marine Environments - Villagra-Blanco, Rudolfo; Silva, Liliana M. R.; Conejeros, Ivan; Taubert, Anja; Hermosilla, Carlos; Justus Liebig University Giessen (My University, 2019)
Leukocytes play a major role in combating infections either by phagocytosis, release of antimicrobial granules, or extracellular trap (ET) formation. ET formation is preceded by a certain leukocyte cell death form, known as ETosis, an evolutionarily conserved mechanism of the innate immune system also observed in marine mammals. Besides several biomolecules and microbial stimuli, marine mammal ETosis is also trigged by various terrestrial protozoa and metazoa, considered nowadays as neozoan parasites, which are circulating in oceans worldwide and causing critical emerging marine diseases. Recent studies demonstrated that pinniped- and cetacean-derived polymorphonuclear neutrophils (PMNs) and monocytes are able to form different phenotypes of ET structures composed of nuclear DNA, histones, and cytoplasmic peptides/proteases against terrestrial apicomplexan parasites, e.g., Toxoplasma gondii and Neospora caninum. Detailed molecular analyses and functional studies proved that marine mammal PMNs and monocytes cast ETs in a similar way as terrestrial mammals, entrapping and immobilizing T. gondii and N. caninum tachyzoites. Pinniped- and cetacean leukocytes induce vital and suicidal ETosis, with highly reliant actions of nicotinamide adenine dinucleotide phosphate oxidase (NOX), generation of reactive oxygen species (ROS), and combined mechanisms of myeloperoxidase (MPO), neutrophil elastase (NE), and DNA citrullination via peptidylarginine deiminase IV (PAD4).This scoping review intends to summarize the knowledge on emerging protozoans in the marine environment and secondly to review limited data about ETosis mechanisms in marine mammalian species.
Keywords: extracellular traps; ETosis; emergingmarine diseases; marinemammals; neozoan parasites; ddc:630